How Do Political Connections of Firms Matter during an Economic Crisis? - Yutong Chen; Gaurav Chiplunkar; Sheetal Sekhri; Anirban Sen; Aaditeshwar Seth (Institute of Labor Economics (IZA), 2023)
We use a new machine learning-enabled, social network based measurement technique to assemble a novel dataset of firms' political connections in India. Leveraging this data along with a long panel of detailed financial transactions of firms, we study how political connections matter during an economic downturn. Using a synthetic difference-in-differences framework, we find that connected firms had 8-10% higher income, sales, and TFPR gains that were persistent for over a three-year period following the crisis. We unpack various mechanisms and show that connected firms were able to delay their short-term payments to suppliers and creditors, delay debt and interest payments, decrease expensive long-term borrowings from banks in favor of short-term non-collateral ones, and increase investments in productive assets such as computers and software. Our method to determine political connections is portable to other applications and contexts.
Keywords: O16; D22; D73; 330; political connections; firms; crisis